Bioindicators to detect pollution from dumping sites and landfills : bioaccumulation in Mytilus edulis and Nucella lapillus in Iceland - Urbschat, Mæva Marlene, 1956- (2013)
This study is an attempt to explain a complex environmental situation at the shore beneath a dumping site in Iceland. Heavy metals, originated outside Iceland, are distributed by oceanic currents and airpollution. Another pathway to Icelandic nature are products, containing heavy metals, which are thrown uncontrolled at dumping sites after use. Today the content of still existing dumping sites around Iceland is unknown, but composition and quantities of different waste-categories can be estimated from the activities during the period, when the waste was produced. From these waste-filled places leachate transports irregulary heavy metals to the marine biota. Bioaccumulated arsen, cadmium, copper, chromium, lead, mercury, zinc were measured in Nucella lapillus, preying on Mytilus edulis and Semibalanus balanoides. The results show higher cadmium concentrations in dogwhelks compared to Gufunes/Reykjavík harbour. Copper and zinc concentrations exceed the Icelandic overall mean. Chromium, copper, zinc concentrations in dogwhelks at this small village overtop values in Irland. Presence of mercury-resistant bacteria in the leachate was confirmed by microbiological test. The anthropogenic impact of the dumping site occurs not in sporadic taken analyses of leachate. The results indicate the vital necessity to registrate all dumping sites, additionally to monitor with bioindicators their impact on aquatic ecosystems. Markmið rannsóknar er að varpa ljósi á mengun í fjöru neðan við gamlan ruslahaug. Þungmálmar, upprunir utan Íslands, dreifast með sjávarstraumum og loftmengun. Önnur flutningsleið þungmálma að íslenskri náttúru er með afurðum sem innihalda þungmálma og var fargað með stjórnlausum hætti á ruslahaugum í lok líftíma afurðanna. Innihald og staðsetningar gamallra ruslahauga á Íslandi eru ekki þekktar. Hægt er að áætla um efnasamsetningu og efnamagn með því að taka mið af framleiðsluaðferðum og neysluvenjum þess tímabils sem ruslahaugarnir urðu til. Sigvatn frá gömlum ruslahaugum seytir óreglulega þungmálmum í ...